GENERATING BOUGUER ANOMALY MAP FROM AIRBORNE GRAVITY DATA (A CASE STUDY IN SOUTH EAST SULAWESI) - Laode M Sabri; Bambang Sudarsono; Jamal Jamal; Sonny Mawardi (Elipsoida : Jurnal Geodesi dan Geomatika, 2020)
Terrestrial measurements can provide accurate gravity data, but it is costly and time-consuming for large and remote area. Airborne gravity measurements have actually been carried out in Indonesia since 2008 by Technical University of Denmark (DTU) in collaboration with the Geospatial Information Agency (BIG). Purpose of the project was to develop a geoid model used for converting elevations from GPS/GNSS measurements that refers to ellipsoid to orthometric elevations that refer to sea level. The data can actually be explored so that it can be used for geophysical and other geoscience purposes, but the data must be carefully treated and extracted into observational gravity data. This study aims to improve the accuracy of gravity airborne data to produce an accurate complete Bouguer anomaly map. The data used in this study were airborne gravity data over Province of Southeast Sulawesi collected on September 29, 2008 to October 1, 2008.  Variation in flight height at the time of consecutive data introduced new horizontal acceleration vector. It must be treated as a noise in the measurement of gravity data. The first stage of processing was to eliminate noise due to aircraft acceleration. Gravity data measured in aircraft conditions accelerating more than 5 m.s-2 were eliminated. In this stage, the gravity data were reduced from 64481 observation points to 4900 observation points. The second stage of processing was low pass filtering to eliminate the remaining surges in gravity data. Airborne gravity data that have been snooped and filtered were then applied to calculate the complete Bouguer anomaly. Visually, a complete Bouguer anomaly map through the enhancement process produced a finer map compared to maps from airborne gravity data without enhancement. Comparison of airborne Bouguer anomaly map and terrestrial Bouguer anomaly maps of Kendari sheet showed a correlation of more than 83%. The conclusion of this study was that the enhancement of the airborne data significantly increases the accuracy and reliability of the airborne gravity data for generating a complete bouguer anomaly map. The results of this study also indicated that the airborne archive data has the potential to be used for geophysical and geosciences purposes in Southeast Sulawesi and Indonesia.